2008
DOI: 10.1098/rsbl.2008.0376
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of expression associated with regions of theDrosophilagenome that lack crossing over

Abstract: The recombinational environment influences patterns of molecular evolution through the effects of Hill-Robertson interference. Here, we examine genome-wide patterns of gene expression with respect to recombinational environment in Drosophila melanogaster. We find that regions of the genome lacking crossing over exhibit elevated levels of expression, and this is most pronounced for genes on the entirely non-crossing over fourth chromosome. We find no evidence for differences in the patterns of gene expression b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
29
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 30 publications
7
29
0
1
Order By: Relevance
“…This prediction is supported by data from sex chromosomes (Berlin and Ellegren 2006;Wykoff et al 2002), mitochondrial genomes (Nachman et al 1994(Nachman et al , 1996Rand and Kann 1996) and Drosophila genomic regions with different recombination rates (Haddrill et al 2007). There is evidence of homologous recombination in DNA viruses (Thiry et al 2004;Wilkinson and Weller 2003) and in both positive strand (Agol 2006;Lukashev 2005;Twiddy and Holmes 2003;Worobey and Holmes 1999) and negative-strand (Hughes 2007;Kukkonen et al 2005;Spann et al 2003) ssRNA viruses.…”
Section: Discussionsupporting
confidence: 60%
“…This prediction is supported by data from sex chromosomes (Berlin and Ellegren 2006;Wykoff et al 2002), mitochondrial genomes (Nachman et al 1994(Nachman et al , 1996Rand and Kann 1996) and Drosophila genomic regions with different recombination rates (Haddrill et al 2007). There is evidence of homologous recombination in DNA viruses (Thiry et al 2004;Wilkinson and Weller 2003) and in both positive strand (Agol 2006;Lukashev 2005;Twiddy and Holmes 2003;Worobey and Holmes 1999) and negative-strand (Hughes 2007;Kukkonen et al 2005;Spann et al 2003) ssRNA viruses.…”
Section: Discussionsupporting
confidence: 60%
“…More recent studies have confirmed the main observation of reduced selection at synonymous sites in regions with strongly reduced rates of recombination, even after correcting for possible nonselective influences on nucleotide composition (Kliman and Hey, 1993a;Comeron et al, 1999;Zurovcova and Eanes, 1999;Comeron and Kreitman, 2002;Hey and Kliman, 2002;Marais and Piganeau, 2002;Marais et al, 2003;Haddrill et al, 2007). It should be noted however that the relationship between codon bias and recombination rate in Drosophila could also be influenced by nonselective factors.…”
Section: Direct and Indirect Evidence Of Hr In Eukaryotesmentioning
confidence: 77%
“…Analyses of rates of protein evolution between Drosophila species show that genes located in genomic regions with strongly reduced recombination have an excess of fixed deleterious mutations and a deficit of fixed advantageous mutations compared to highly recombining genomic regions (Hilton et al, 1994;Takano, 1998;Comeron and Kreitman, 2000;Betancourt and Presgraves, 2002;Zhang and Parsch, 2005;Haddrill et al, 2007). Also, the study of recent nonrecombining chromosomes (for example, neo-Y chromosome in Drosophila miranda) reveals an equivalent pattern with reduced effectiveness of selection (Bachtrog and Charlesworth, 2002;Bachtrog, 2003).…”
Section: Direct and Indirect Evidence Of Hr In Eukaryotesmentioning
confidence: 99%
“…In species with a smaller N e , selection plays a less important role, causing slightly deleterious mutations to be fixed at an elevated rate. The same pattern is repeated across genomic regions with smaller N e , such as regions with low recombination, in which linkage between weakly selected loci reduces the effectiveness of selection (Haddrill et al, 2007;Presgraves, 2005). Conversely, temporally increased substitution rates have also been found in lineages that had undergone population size expansions, due to the fixation of slightly advantageous back-mutations (Charlesworth and Eyre-Walker, 2007).…”
Section: The Molecular Clock Age Estimates and The Fossil Recordmentioning
confidence: 83%